It takes a rake - Bennett, Anna (Romance novelist) (Bennett, Anna (Romance novelist). Rogues to lovers, 2024)
"She's about to face her biggest challenge yet... Since she was a girl, Miss Kitty Beckett has been adept at finding trouble: sneaking brandy, running away, and getting under the skin of the boy who, like her, was an apprentice to an architect. Now Kitty's a talented heiress who can take a dry building plan and breathe life into it with her pencils and paints. Also? She can spot a rake at a hundred yards--and she won't be tricked or charmed into marriage. Certainly not by a man who might interfere with her dreams. When Bellehaven Bay announces its first ever architectural design contest, she vows to win--with a little help from her childhood rival. Turning her buttoned-up nemesis into a certified rake. Leo Lockland, a hardworking architect with a gift for numbers, has returned home after a few years in London, and he has secrets. The biggest? He's been in love with Kitty since they were both apprentices. She refuses to give her heart to any man, but Leo's determined to beat the odds--even if it means learning how to be a rake. Fortunately, Kitty's willing to tutor him in the nuances of fashion, flirtation, and seduction in exchange for his help with the contest. But the whole plan would fall apart if she knew how he felt, so he'll have to be very convincing. Let the lessons begin... Leo proves to be a surprisingly quick study in the ballroom, on the beach, and in the bedchamber. Before long, he's softening Kitty's hard edges with his wicked words and kissing his way past all her defenses. Perhaps she's a bit too skilled at teaching, because her lessons are threatening to backfire, putting her closely guarded heart in grave danger..."--Publisher's website.